Geo-Congress 2019. selected papers from sessions of the Eighth International Conference on Case Histories in Geotechnical Engineering : March 24-27, 2019, Philadelphia, Pennsylvania - Meehan, Christopher L.; Kumar, Sanjeev, 1964-; Pando, Miguel Angel, 1968-; Coe, Joseph T. (American Society of Civil Engineers, 2019)
Selected papers from sessions of the Eighth International Conference on Case Histories in Geotechnical Engineering, held in Philadelphia, Pennsylvania, March 24-27, 2019. Sponsored by the Geo-Institute of ASCE. This Geotechnical Special Publication contains 33 peer-reviewed papers on soil erosion, underground engineering, and risk assessment. Topics include: soil deformation, scour, and piping; monitoring and rehabilitation techniques; geohazards and extreme weather; case studies; and tunneling and underground construction. GSP 313 will be of interest to practitioners and researchers involved in underground engineering.
Keywords: Geotechnical engineering -- Congresses.; Geotechnical engineering -- Case studies.; Geotechnical engineering -- Risk assessment -- Congresses.; Soil erosion -- Congresses.; Underground construction -- Congresses.; Geotechnical engineering -- Risk assessment -- Case studies.; Soil erosion -- Case studies.; Underground construction -- Case studies.; elektronické knihy; electronic books